In vitro Anticancer Activity of Marine Sponges Against T47D and HeLa Cell Lines: In vitro Anticancer Activity of Marine Sponges Against T47D - Suciati, -; Arifianti, Lusiana (Dhaka University Journal of Pharmaceutical Sciences, 2020)
Marine sponges have been known as the source of natural products. Various metabolites with potent bioactivities have been reported from this organism. The current study aims to investigate the anticancer potency of three marine sponges namely Diacarnus debeauforti, Haliclona amboinensis and Agelas cavernosa collected from Barrang Lompo Island, South Sulawesi, Indonesia. The ethyl acetate extracts of the sponges were screened against T47D breast cancer cells and HeLa cervical cancer cells by using the MTT method. The results showed that these sponges demonstrated anticancer activity against both cancer cell lines. The lowest IC50 of 18.2 μg/ml was given by the extract of A. cavernosa against T47D cell line, while in the screening against HeLa cancer cell line, the extract of D. debeauforti revealed the highest potency with IC50 of 15.7 μg/ml. Our results suggested that the marine sponges namely D. debeauforti, H. amboinensis and A. cavernosa can be good candidates for the development of anticancer agents. Dhaka Univ. J. Pharm. Sci. 19(1): 25-28, 2020 (June)